PLECHAR – Morphological and anatomical character information for 661 pleurocarpous mosses for use in evolutionary and ecological studies - Hedenäs, Lars (Swedish Museum of Natural History, 2025)
The data file PLECHAR.xlsx (Excel) includes four sheets
• SPECIES AND CHARACTER STATES, with the data.
• STUDIED SPECIMENS, specifying which specimens were studied.
• CITED LITERATURE, listing the literature cited in the PLECHAR.xlsx file itself.
• CHARACTER EXPLANATIONS – READ!, with information about characters that are not self-explanatory.

The data (SPECIES AND CHARACTER STATES) includes morphological and anatomical character information for 661 pleurocarpous moss taxa, mostly at the species level, described under 106 headings. I compiled the morphological and anatomical character data for pleurocarpous mosses mainly from studies where I scored the character information myself. Information about which studies this is based on is included in the README file. A few additions were made from the literature, as indicated in the sheet CITED LITERATURE in the data file. Since I scored almost all information myself, any observational bias should be approximately the same throughout the data and the information on a particular character should be comparable between taxa.

Datafilen PLECHAR.xlsx (Excel) innehåller fyra blad
• SPECIES AND CHARACTER STATES, med själva data.
• STUDIED SPECIMENS, en lista med de kollekter som studerats.
• CITED LITERATURE, en lista med litteratur som citeras i filen PLECHAR.xlsx.
• CHARACTER EXPLANATIONS – READ!, med information om karaktärer som kan vara svåra att förstå.

Själva data (SPECIES AND CHARACTER STATES) består av morfologisk och anatomisk information för 661 pleurokarpa bladmossor, oftast på artnivå, beskrivet under 106 rubriker. Jag har samlat den morfologiska och anatomiska informationen för pleurokarpa bladmossor i huvudsak från studier där jag själv har observerat karaktärerna. Information om vilka dessa studier är finns i README-filen. Ett fåtal kompletteringar ur litteraturen finns med bland data, och litteraturkällorna till dessa finns i bladet CITED LITERATURE i datafilen. Eftersom jag gjort nästan alla observationer själv bör förekommande observationsbias vara ungefär den samma i hela datasetet, varför information om en specifik karaktär bör vara jämförbar mellan arter.
PLECHAR – Morphological and anatomical character information for 661 pleurocarpous mosses for use in evolutionary and ecological studies
Keywords: plant ecology; växtekologi; plant morphology; plant anatomy; växtanatomi; phylogeny; fylogeni; bryophytes; hypnales; hookeriales; Ecology; Ekologi; Biological Systematics; Biologisk systematik